Estudo da concentração plasmática de fatores neurotróficos (BDNF,NGF e GDNF) em pacientes com transtorno bipolar do humor - Izabela Guimaraes Barbosa (2009)
Introduction: Bipolar disorder (BD) is a prevalent and chronic illness associated with substantial morbidity. There is a growing body of evidence indicating that alterations in neurotrophic factors, mainly in brain-derived neurotrophic factor (BDNF), may play a role in the pathophysiology of BD. Objective The aim of this study was to examine neurotrophic factors plasma levels (BDNF, NGF and GDNF) in BD patients, type I, compared with drug-free healthy controls and theirrelationship with comorbitidies and medications in use. Methods: We measured plasma neurotrophic factor (BDNF, NGF e GDNF) concentration by an enzyme linked immunosorbent assay methods in 74 subjects, including 21 drug-free healthy controls, 53 patients with bipolar disorder, type I (19 euthymic patients and 34 in current maniacepisode). At the time of the study, no one the subjects were in treatment with corticosteroids, antibiotics or anti-inflammatory for at least four weeks. Results: Compared to healthy controls, plasma concentrations GDNF (p=0,395) and NGF (p=0,795) theres no significant difference in the patients group. Plasma BDNF concentrations, compared to healthy controls, were significantly increased in patients with mania and euthymia (p=0,001) with no significant difference among them. Drug treatments, comorbid psychiatric disorders, clinical disorders, age, years of study, maniac symptoms or psychosis had no effect on elevated circulating BDNF in affective patients. BDNF was elevated only in those patients in bipolar disorder whose first episode of humor was at least 10 years previous at the study (p=0,049). Conclusions: Present results demonstrated reduced circulation plasma BDNF levels in patientswith BD, for the first time, mainlining in patients with longer than 10 years since the first episode of humor. Our findings suggest the role of BDNF in the pathophysiology of BD, like other findings in literature.